Phenomena Conflict, Anxiety, and Depression for Cancer Survivor One Year and After Have Therapy in General Hospital - Turnip, Maria; Keliat, Budi Anna; Eka Putri, Yossie Susanti (Jurnal NERS, 2015)
Introduction. Psychosocial distress emerges in cancer disease. This research explores experience of conflict, anxiety, and depression in one year cancer survivor. Methods. Data were collected through in-depth semi structured interviews with fifteen participants when seeking treatment at a public hospital in Bandung. Result. There nine themes emerge: anxiety about cancerâs spread and recurrence, changing relationships with a partner, labeling from oneself and others, physical discomfort along treatment, psychological discomfort along treatment, self-concept, religious/spiritual, hiding diagnose and complain, and deficit information about cancer. But, four themes among were not characterized with conflict, anxiety, and depression. Conflict, anxiety, and depression impact condition of the client cancer. Discussion. Experience of conflict, anxiety, and depression became the basis for the development of management system service and provision of facilities for integrated mental health nursing therapy.Key word: cancer, conflict, anxiety, depression